Respuesta :

b) 1/3x + 1/3x=2/3x
-1/4y - 1/4y= -1/2y

Answer:

Option B

Step-by-step explanation:

To find expression is equivalent to [tex]\frac{2}{3}x-\frac{1}{2}y-\frac{4}{5}[/tex] we will go through all the options.

Option A.

[tex]\frac{1}{3}x-\frac{1}{4}^y-\frac{4}{5}+\frac{1}{3}x+\frac{1}{4}y[/tex]

[tex]=x(\frac{1}{3}+ \frac{1}{3})- y(\frac{1}{4}- \frac{1}{4})-\frac{4}{5}[/tex]

[tex]=\frac{2}{3}x-\frac{4}{5}[/tex]

Option B.

[tex]\frac{1}{3}x-\frac{1}{4}y-\frac{4}{5}+\frac{1}{3}x-\frac{1}{4}y[/tex]

[tex]=x(\frac{1}{3}+ \frac{1}{3})-y(\frac{1}{4}+ \frac{1}{4})\frac{-4}{5}[/tex]

[tex]=\frac{2}{3}- \frac{1}{2}y-\frac{4}{5}[/tex]

Option C.

[tex]\frac{1}{3}x- \frac{1}{4}y- \frac{1}{5}- \frac{1}{3}x- \frac{3}{5} -\frac{1}{4}y[/tex]

[tex]x(\frac{1}{3} -\frac{1}{3})-y(\frac{1}{4} +\frac{1}{4})-(\frac{1}{5}+ \frac{3}{5})[/tex]

[tex]=-\frac{1}{2}y- \frac{4}{5}[/tex]

Option D.

[tex]\frac{1}{3}x-\frac{1}{4}y+ \frac{2}{5}+ \frac{1}{3}x- \frac{2}{5}- \frac{1}{4}y[/tex]

[tex]=x(\frac{1}{3}+ \frac{1}{3})-y(\frac{1}{4} +\frac{1}{4})+(\frac{2}{5}- \frac{2}{5})[/tex]

[tex]=\frac{2}{3}x- \frac{1}{2}y[/tex]

Therefore, Option B is the answer.

ACCESS MORE